Ship breaker - Bacigalupi, Paolo (New York : Little, Brown, 2010)
In a futuristic world, teenaged Nailer scavenges copper wiring from grounded oil tankers for a living, but when he finds a beached clipper ship with a girl in the wreckage, he has to decide if he should strip the ship for its wealth or rescue the girl.
Booklist starred
School Library Journal
Wilson's Senior High School
Booklist starred, May 2010
Bulletin (Center for Children's books), June 2010
Horn Book Starred, July 2010
Keywords: Conduct of life -- Juvenile fiction; Recycling (Waste) -- Juvenile fiction; Conduct of life -- Fiction; Recycling (Waste) -- Fiction; Science fiction; Conduct of life -- Fiction; Recycling -- Fiction; Science fiction; Science fiction